The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10529-013-1313-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-intensity pulsed ultrasound on cell viability, proliferation and neural differentiation of induced pluripotent stem cells-derived neural crest stem cells

Abstract: Low-intensity pulsed ultrasound (LIPUS) acting on induced pluripotent stem cells-derived neural crest stem cells (iPSCs-NCSCs) is considered a promising therapy to improve the efficacy of injured peripheral nerve regeneration. Effects of LIPUS on cell viability, proliferation and neural differentiation of iPSCs-NCSCs were examined respectively in this study. LIPUS at 500 mW cm(-2) enhanced the viability and proliferation of iPSCs-NCSCs after 2 days and, after 4 days, up-regulated gene and protein expressions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 41 publications
2
63
2
Order By: Relevance
“…However, the optimal therapeutic intensity of LIPUS acted on the nerve conduit in vivo is still unclear. Our previously study (Lv et al 2013) proved that LIPUS at 0.3 and 0.5 W cm -2 could enhance the viability and proliferation of iPSCsNCSCs. Tsuang et al (2011) also demonstrated that 0.3 W cm -2 LIPUS could promote Schwann cells proliferation and prevent cell death in a severely injured peripheral nerve.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…However, the optimal therapeutic intensity of LIPUS acted on the nerve conduit in vivo is still unclear. Our previously study (Lv et al 2013) proved that LIPUS at 0.3 and 0.5 W cm -2 could enhance the viability and proliferation of iPSCsNCSCs. Tsuang et al (2011) also demonstrated that 0.3 W cm -2 LIPUS could promote Schwann cells proliferation and prevent cell death in a severely injured peripheral nerve.…”
Section: Discussionmentioning
confidence: 84%
“…The regenerated neurons also could secrete some growth factors such as neural growth factor (NGF) and brained-derived neural growth factor (BDNF), which were benefit for the reconstruction of synapses. In our previously study (Lv et al 2013), the gene and protein Fig. 7 Immunostaining of Tuj1 of sciatic nerve in the cross section of nerve conduit at 5-7 mm from the proximal end at 3 months post-implantation.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations